Conservation relationship bridging entropy and information - Stoyan C. Russev (Physics Open)
Entropy and information are interconnected concepts fundamental to physics and information theory with reflections in different fields like biology, computer science, cosmology, information technology, even social science and law. However, a generally accepted quantitative link between them is still missing. This study addresses the fundamental relationship between physical entropy and information. It is shown here that there is a simple and universal conservation relationship between physical entropy and appropriately interpreted information entropy. As an illustration of its application, it is demonstrated that Landauer's lower bound on entropy change can be directly derived from this relationship.